Apakah Pengetahuan, Sikap dan Dukungan Suami Berpengaruh terhadap Niat Melakukan Pap Smear di Rumah Sakit? - Arif Nugroho Triutomo; Anisa Catur Wijayanti (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: Estimated number of cases of cervical cancer in Indonesia is estimated as many as 98,692 cases in 2013. Based on prevalence, D.I.Yogyakarta Province has the biggest prevalence in Indonesia that is 0.41%. Pap smear is one of the tests to determine the presence of malignancy in the cervical epithelium which is an early sign of cervical malignancy. The purpose of this study is to analyze the influence of knowledge, attitudes and support of the husband to the intention of pap smear examination in RSKIA Adinda Yogyakarta. Method: The research method used is analytical research with cross sectional approach. The population used was all female patients aged 15-49 years old who visited the RSKIA Adinda Yogyakarta clinic with a sample size of 147 people. Sampling by purposive sampling. The analysis used with chi square Result: The result of statistical test shows that there is influence between knowledge (p = 0,000), attitude (p = 0,000) and husband support (p = 0,000) with intention to check pap smear at RSKIA Adinda Yogyakarta. So it can be concluded there is influence of knowledge, attitude and support of husband to intention of examination of pap smear at RSKIA Adinda Yogyakarta. Implication: It is expected that the husband will participate in conducting examinations or health consultations related to pap smears so that the husband can participate in helping to provide support, solutions or opinions to the wife about the pap smear test.